The role of turbulence and internal waves in the structure and evolution of a near-field river plume - Rebecca A. McPherson; Craig L. Stevens; Joanne M. O'Callaghan; Andrew J. Lucas; Jonathan D. Nash (Ocean Science, 2020)
An along-channel momentum budget is quantified in the near-field plume region of a controlled river flow entering Doubtful Sound, New Zealand. Observations include highly resolved density, velocity and turbulence, enabling a momentum budget to be constructed over a control volume. Estimates of internal stress (τ) were made from direct measurements of turbulence dissipation rates (ϵ) using vertical microstructure profiles. High flow speeds of the surface plume over 2 m s−1 and strong stratification (N2∼10-1 s−2) resulted in enhanced turbulence dissipation rates (ϵ>10-3 W kg−1) and internal stress (τ>10-2 m2 s−2) at the base of the surface layer. Internal waves were observed propagating along the base of the plume, potentially released subsequent to a hydraulic jump in the initial 1 km downstream of the plume discharge point. The momentum flux divergence of these internal waves suggests that almost 15 % of the total plume momentum can be transported out of the system by wave radiation, therefore playing a crucial role in the redistribution of momentum within the near-field plume. Observations illustrate that the evolution of the momentum budget components vary between the distinct surface plume layer and the turbulent, shear-stratified interfacial layer. Within the surface plume, a momentum balance was achieved. The dynamical balance demonstrates that the deceleration of the plume, driven by along-channel advection, is controlled by turbulence stress from the plume discharge point to as far as 3 km downstream. In the interfacial layer, however, the momentum equation was dominated by the turbulence stress term and the balance was not closed. The redistribution of momentum within the shear-stratified layer by internal wave radiation and other hydraulic features could account for the discrepancy in the budget.